2017
DOI: 10.2134/agronj2017.04.0209
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated Corn Productivity as Influenced by Nitrogen Source, Rate, and Climatic Conditions

Abstract: Core Ideas Polymer coated N fertilizer was effective in improving crop yields. Chemical inhibitors used in the study was not effective in reducing environmental N losses. Varieties of available different chemical inhibitors may act differently and need to be compared and contrasted. Nitrogen fertilizer modifications such as coating or chemical additives are designed to either slow or inhibit N transformation, thereby to improve grain yield (GY) and reduce N losses. Effectiveness of these specialized products d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
1
18
2
Order By: Relevance
“…Ferrel (2012) observed a 300% increase in soil NH 4 -N concentration when utilizing the NI dicyandiamide (DCD) as compared to Instinct. Maharjan et al (2017) observed no corn yield benefits to Instinct application despite significant rainfall occurring the day of N application and in the two weeks following N application. Previous research has observed poor Instinct performance across various cropping systems and environmental conditions (Ferrel, 2012;Franzen, 2017;Maharjan et al, 2017;Sassman et al, 2018) with authors attributing poor performance to inadequate nitrapyrin availability from microencapsulation (Ferrel, 2012;Franzen, 2017;Maharjan et al, 2017).…”
Section: Nitrification Inhibitormentioning
confidence: 80%
See 3 more Smart Citations
“…Ferrel (2012) observed a 300% increase in soil NH 4 -N concentration when utilizing the NI dicyandiamide (DCD) as compared to Instinct. Maharjan et al (2017) observed no corn yield benefits to Instinct application despite significant rainfall occurring the day of N application and in the two weeks following N application. Previous research has observed poor Instinct performance across various cropping systems and environmental conditions (Ferrel, 2012;Franzen, 2017;Maharjan et al, 2017;Sassman et al, 2018) with authors attributing poor performance to inadequate nitrapyrin availability from microencapsulation (Ferrel, 2012;Franzen, 2017;Maharjan et al, 2017).…”
Section: Nitrification Inhibitormentioning
confidence: 80%
“…Despite significant rainfall following N application, NI application did not affect grain yield at either 2017 location. In spite of above average rainfall, insignificant responses to NI application following N fertilization have been observed in recent literature (Barker and Sawyer, 2017;Franzen, 2017;Maharjan et al, 2017;Sassman et al, 2018). Barker and Sawyer (2017) observed no soil NO 3 -N or corn grain yield benefits from NI application on fine-textured, poorly drained soils receiving 10.7 cm rainfall within one week of N application.…”
Section: Nitrification Inhibitormentioning
confidence: 98%
See 2 more Smart Citations
“…However, few studies have reported significant increases in grain yields. One exception was Maharjan et al (2017) who observed grain yield increases with application of UAN and nitrapyrin only in one out of two years when rainfall was relatively lower. The NI might not have had significant effects on yields in those studies since they were conducted with irrigated systems and NI typically works best in soils that experience saturated conditions.…”
Section: Introductionmentioning
confidence: 98%